Ontogeny specification and epigenetic regulation of macrophage plasticity - Huang, Han-Ying; Zheng, Xin-Nan; Tian, Lin (Frontiers in Immunology, 2025)
Macrophages are ubiquitously distributed across tissues, playing pivotal roles in maintaining homeostasis under physiological conditions and modulating disease progression in pathological contexts. Although the classic M1/M2 classification of macrophage polarization provides a useful framework, it significantly oversimplifies the plasticity and heterogeneity of these cells. Recent advances that combine lineage tracing with multi-omic profiling have unveiled new insights into macrophage functional specification. In this mini-review, we examine how ontogeny, environmental cues, and genetic as well as epigenetic factors converge to drive macrophage plasticity through epigenetic reprogramming. Additionally, we highlight cutting-edge in situ profiling techniques that facilitate the study of macrophages within their native tissue microenvironment. A deeper understanding of macrophage plasticity promises to elucidate fundamental regulatory mechanisms and uncover novel therapeutic targets, paving the way for transformative disease treatments.